A Preliminary Experimental Study on Inherent Association of Verbs to Specific Nouns - I Gede Semara Dharma Putra; Gede Primahadi Wijaya Rajeg (Humanitatis : Journal of Language and Literature, 2024)
Collocations, or word co-occurrences, are typically studied based on written corpus data. In this paper, we used preliminary experimental data to explore the inherent association between a verb and certain nouns. We hypothesized that specific verbs would vary with respect to the nouns the verbs are associated with. To test this hypothesis, we developed an experiment using the Gorilla Experiment Builder to simulate the preference selection of nouns with each verb. The research was done with a sample size of 17 participants and each of them performed 35 trials inside the Gorilla software. The responses were compiled into a set of tables as the basis for generating bar plots, showing the frequency of nouns selected with each verb. The overall results show that the studied verbs have certain preferences towards specific nouns. Even though this research found initial support for the hypothesis, the findings are not conclusive due to the small sample size of participants, being far from the population size initially measured. We discuss a way to corroborate the findings using different methods.